Peran Islam dalam Perkembangan Masyarakat Multikultural di Australia - Muhammad Arif Wicaksono; Eko Ribawati (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
The course of Islamic history on the Australian continent has undergone development over time. The entry of Islam in Australia was marked by contact between fishermen from South Sulawesi and the natives of Northern Australia around 1600. This first contact was motivated by South Sulawesi traders who were looking for sea cucumbers. The development of Islam in Australia after the contact became more widespread to form a multicultural society. This is motivated by the large number of immigrants who enter the Australian region to work and earn a living. The Muslim community in Australia is experiencing various adaptation processes in Australia to be able to blend in with the multicultural society in Australia This research was made with the aim of explaining the role of Islam in the multicultural society in Australia. interpretation and expressed in the form of historiography writing.